2016
DOI: 10.1111/bor.12160
|View full text |Cite
|
Sign up to set email alerts
|

Surge dynamics of Aavatsmarkbreen, Svalbard, inferred from the geomorphological record

Abstract: This study investigated the surge dynamics of Aavatsmarkbreen, a glacier in Svalbard and its geomorphological impact based on remote sensing data and field observations. The main objective was to analyse and classify subglacial and supraglacial landforms in the context of glacial deformation and basal sliding over a thin layer of thawed, water‐saturated deposits. The study also focused on the geomorphological evidence of surge‐related sub‐ and supraglacial crevassing and glacier front fracturing. From 2006 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 77 publications
2
17
0
Order By: Relevance
“…A connection between glacier surging and till has been established through the observation of till in the forefield of surging glaciers (e.g., Christoffersen et al, ; Evans & Rea, ; Sobota et al, ), through borehole and geophysical observations of the subglacial environment (e.g., Blake et al, ; Harrison & Post, ; Porter et al, ; Truffer et al, ), and through the study of basal ice facies (Sharp et al, ). Till displays both pseudoviscous and Coulomb behavior (e.g., Iverson et al, ; Rathbun et al, ), allowing it to deform plastically above the yield strength, with recoverable elastic strain dominating below the yield strength.…”
Section: Discussionmentioning
confidence: 99%
“…A connection between glacier surging and till has been established through the observation of till in the forefield of surging glaciers (e.g., Christoffersen et al, ; Evans & Rea, ; Sobota et al, ), through borehole and geophysical observations of the subglacial environment (e.g., Blake et al, ; Harrison & Post, ; Porter et al, ; Truffer et al, ), and through the study of basal ice facies (Sharp et al, ). Till displays both pseudoviscous and Coulomb behavior (e.g., Iverson et al, ; Rathbun et al, ), allowing it to deform plastically above the yield strength, with recoverable elastic strain dominating below the yield strength.…”
Section: Discussionmentioning
confidence: 99%
“…Several unnamed minor tributaries join the upper half of the main trunk above 250 m a.s.l. Recent observations at the margins of Aavatsmarkbreen have revealed that the glacier is resting on a thin layer of glacial deposits (up to 0.5 m; Sobota et al, ).…”
Section: Study Areasmentioning
confidence: 99%
“…; Sobota et al . ). These studies have provided new insights into past glacial and climatic changes in western Spitsbergen.…”
mentioning
confidence: 97%
“…Several of these have been inferred to be of surge type, implying that they experience cyclical changes in their flow velocities, triggered by internal mechanisms rather than external forcing, such as climate change (Lefauconnier & Hagen 1991;Solheim 1991;Hagen et al 1993;Ottesen & Dowdeswell 2006;Ottesen et al 2008;Blaszczyk et al 2009;Flink et al 2015;Streuff et al 2015). The dynamics and recent glacial history of the tidewater glaciers in the fjords of western Spitsbergen have been relatively well studied using marine geophysical, sedimentological, remote sensing and field-based methods (Vieli et al 2002;Hald et al 2004;Plassen et al 2004;Ottesen & Dowdeswell 2006;Ottesen et al 2008;Kristensen et al 2009;Baeten et al 2010;Mansell et al 2012;Blaszczyk et al 2013;Kempf et al 2013;Burton et al 2015;Flink et al 2015;Streuff et al 2015;Sobota et al 2016). These studies have provided new insights into past glacial and climatic changes in western Spitsbergen.…”
mentioning
confidence: 99%